2021
DOI: 10.3390/jcm10040664
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Risk and Predictors of Sleep Disorders in Patients with Psoriasis—A Questionnaire-Based Cross-Sectional Analysis

Abstract: Psoriasis is a chronic, inflammatory skin disease affecting 2–4% of the general population. Accompanying subjective symptoms (pruritus or pain) may cause decreased life quality including sleep disorders (SD). Sixty psoriatic patients fulfilled the following questionnaires: Pittsburgh Sleep Quality Index (PSQI), STOP BANG for the obstructive sleep apnea syndrome (OSAS) assessment, and Restless Legs Syndrome (RLS) Severity Scale. Patients’ laboratory and clinical data were also investigated. All data obtained we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
3
26
1
1
Order By: Relevance
“…Among all SD in such patients, RLS is probably the least studied and uncertain. Nevertheless, in our previous research, we proved that patients with psoriasis had more severe symptoms of RLS (6). Similar outcomes are obtained by Saçmaci et al (7).…”
Section: The Influence Of Psoriasis On Rlssupporting
confidence: 89%
See 2 more Smart Citations
“…Among all SD in such patients, RLS is probably the least studied and uncertain. Nevertheless, in our previous research, we proved that patients with psoriasis had more severe symptoms of RLS (6). Similar outcomes are obtained by Saçmaci et al (7).…”
Section: The Influence Of Psoriasis On Rlssupporting
confidence: 89%
“…We also found that such patients slept significantly fewer hours and took more sleeping medications. Therefore, we believed that SD should be taken into account in daily clinical practice, and reliable recommendations regarding its early detection should be established ( 6 ).…”
Section: The Influence Of Psoriasis On Sleep Coursementioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that about 30% of patients will develop psoriatic arthritis [ 3 ]. Other disorders occurring more frequently in psoriatic patients are inflammatory bowel diseases, neoplasms, and neurodegenerative and sleep disorders [ 4 , 5 ]. Nevertheless, the most thoroughly investigated and closest relationship of PSO is probably that with metabolic syndrome (MS) and other cardiometabolic diseases (CMDs) [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having psoriasis has, in varying degree, been associated with an elevated risk of cardiovascular (CV) disease [ 5 ]. This is in part related to the high prevalence of CV risk factors in psoriasis, in particular hypertension and obesity [ 5 , 6 ]. In a British registry of patients with moderate to severe psoriasis receiving biological systemic treatment, 73% of patients were overweight or obese and 31% had hypertension [ 7 ].…”
Section: Introductionmentioning
confidence: 99%